2014
DOI: 10.1038/jid.2013.274
|View full text |Cite
|
Sign up to set email alerts
|

Warm, Humid, and High Sun Exposure Climates Are Associated with Poorly Controlled Eczema: PEER (Pediatric Eczema Elective Registry) Cohort, 2004–2012

Abstract: Anecdotal reports of children experiencing eczema flares during winter and summer months along with global variation in eczema prevalence has fueled speculation that climate may modulate disease activity. The aim of this study was to determine if long-term weather patterns affect the severity and persistence of eczema symptoms in children. We performed a prospective cohort study of U.S. children (N=5,595) enrolled in PEER (Pediatric Eczema Elective Registry) between 2004 and 2012 to evaluate the effect of clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
2
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 43 publications
(51 reference statements)
4
63
2
5
Order By: Relevance
“…A Spanish study of children aged 6 to 7 years found an inverse association between childhood AD and mean annual number of sunny hours [85]. However, a prospective cohort study found greater long-term sun exposure to be associated with poorly controlled disease [88].…”
Section: 42mentioning
confidence: 99%
See 4 more Smart Citations
“…A Spanish study of children aged 6 to 7 years found an inverse association between childhood AD and mean annual number of sunny hours [85]. However, a prospective cohort study found greater long-term sun exposure to be associated with poorly controlled disease [88].…”
Section: 42mentioning
confidence: 99%
“…Yet, until recently, there was little evidence to support this notion. One study found that relocating children with AD from the home subarctic/temperate climate of Norway to a subtropical climate in Gran Canary for 4 weeks improved skin symptoms and quality of life [3,[83][84][85][86][87][88]. The climate in a given geographic location is determined by a combination of multiple factors, including temperature, humidity, and precipitation, as well as related factors, such as ultraviolet (UV) exposure.…”
Section: Climatementioning
confidence: 99%
See 3 more Smart Citations